2017
DOI: 10.5005/jp-journals-10032-1119
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Black South African Women toward Menopause: Impact of Culture and Traditions

Abstract: Introduction Vasomotor symptoms of menopause could affect the quality-of-life of most women. The understanding of menopause by African women and the coping mechanisms of these women are essential factors that may be influenced by culture and traditions. This study has evaluated the psychosomatic and sociodemographic profiles of menopausal black South African women in order to ascertain the role played by their culture and traditions during the menopausal years. Materials and methods The study was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although women may describe mood changes, sleep disturbance and decreased libido (Nelson 2008), women's experiences of the menopause are deeply shaped by-and inform-a range of biological, socio-economic and cultural circumstances (Winterich and Umberson 1999;Skrzypulec et al 2010;Nusrat et al 2008;Lock 1994). The menopause is not a universally negative experience, and some women report the menopause as a time when they may find greater freedom and growth (de Salis et al 2018;Matsela et al 2017). The influential work by anthropologists Lock and Kaufert compared women's experience in Japan with North America and suggested that different experiences can be understood as 'local biologies' (Lock 1994;Lock and Kaufert 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although women may describe mood changes, sleep disturbance and decreased libido (Nelson 2008), women's experiences of the menopause are deeply shaped by-and inform-a range of biological, socio-economic and cultural circumstances (Winterich and Umberson 1999;Skrzypulec et al 2010;Nusrat et al 2008;Lock 1994). The menopause is not a universally negative experience, and some women report the menopause as a time when they may find greater freedom and growth (de Salis et al 2018;Matsela et al 2017). The influential work by anthropologists Lock and Kaufert compared women's experience in Japan with North America and suggested that different experiences can be understood as 'local biologies' (Lock 1994;Lock and Kaufert 2001).…”
Section: Introductionmentioning
confidence: 99%